Almost flying - Arlow, Jake Maia (Dial Books for Young Readers, 2021)
Future stepsisters, Dalia and Alexa, embark on a roadtrip and when Alexa reveals that her girlfriend will be joining, Dalia promises to keep her secret, but realizes she may have one of her own.